2022
DOI: 10.36660/abc.20210416
|View full text |Cite
|
Sign up to set email alerts
|

Índice Imunoinflamatório Sistêmico como Determinante de Carga Aterosclerótica e Pacientes de Alto Risco com Síndromes Coronarianas Agudas

Abstract: Fundamento: O índice imunoinflamatório sistêmico (IIS), derivado das contagens de neutrófilos, plaquetas e linfócitos, representa o equilíbrio homeostático entre os estados inflamatório, imune e trombótico. O IIS é superior a índices como a relação neutrófilos-linfócitos no prognóstico de várias malignidades, além de ser um melhor preditor de futuros eventos cardíacos que os fatores de risco tradicionais após a intervenção coronariana. Objetivos: Este estudo objetivou avaliar a relação do IIS com a carga atero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…Huang et al found a positive correlation between SII and Gensini score [ 54 ]. Demet Ozkaramanli Gur et al also confirmed a positive correlation between SII and SYNTAX [ 55 ]. Some researchers have begun to combine SII with other relevant indicators to enhance its predictive value.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Huang et al found a positive correlation between SII and Gensini score [ 54 ]. Demet Ozkaramanli Gur et al also confirmed a positive correlation between SII and SYNTAX [ 55 ]. Some researchers have begun to combine SII with other relevant indicators to enhance its predictive value.…”
Section: Discussionmentioning
confidence: 91%
“…From PubMed, Embase, Web of Science, and The Cochrane database, a total of 604 records were obtained. By manual retrieval, two more articles were added, resulting in a total of 8 studies that met the eligibility criteria for analysis based on inclusion and exclusion criteria [ 16 , 18 , 25 30 ]. Figure 1 presents the flowchart outlining the process of study selection and the reasons for exclusion after a full-text examination.…”
Section: Resultsmentioning
confidence: 99%
“…Zuin et al [ 37 ] found a significant relationship between the NLR and the patients’ SxS and its association with 1-year cardiovascular mortality in STEMI or NSTEMI patients treated with PCI within 24 h. Li et al [ 14 ] claimed that new SII biomarkers, including NLR and SII, had better predictive value for MACE and similar predictive value for overall mortality compared to the SxS in NSTEMI patients. Gur et al [ 38 ] demonstrated that a high SII was an indicator of a longer hospital stay and a greater atherosclerotic burden in high-risk patients with ACS in addition to well-known risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory markers have been frequently used to determine the severity, morbidity, and mortality of CVD. High values of NLR and SII have been reported as determinants of subclinical inflammation and shown to be independent predictors of cardiovascular events and mortality in NSTEMI and STEMI [ 14 , 38 , 39 ]. Additionally, both markers have been found to correlate significantly with the SxS, suggesting their predictive ability for severe atherosclerosis and mortality in ACS patients [ 38 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 O índice imuno-inflamatório sistêmico (IIS) tem sido avaliado como um biomarcador facilmente acessível e de baixo custo para estratificar a gravidade da doença arterial coronariana. [6][7][8] O IIS é calculado de acordo com a fórmula: (neutrófilo x plaqueta)/linfócito. Em pacientes com infarto agudo do miocárdio, com ou sem elevação do segmento ST, ou angina, valores elevados de IIS foram associados a maior extensão da lesão aterosclerótica e do dano tecidual, e aumento do tempo de hospitalização.…”
Section: Palavras-chaveunclassified